Sodium ferric phosphate pyrophosphate material with mesoporous structure as well as preparation method and application of sodium ferric phosphate pyrophosphate material
Preparation of sodium ferrophosphate precursor by spray drying, solid phase or sol-gel method, and combined with pre-calcination and thermal shock treatment, the problem of difficult formation of mesoporous structure of sodium ferrophosphate material during sintering is solved. , realizes the rapid preparation of sodium ferric pyrophosphate materials with high capacity and excellent electrochemical properties.
Patent Information
- Application Number
- CN202411055545.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-02
- Publication Date
- 2024-12-17
AI Technical Summary
It is difficult for existing sodium ferric pyrophosphate materials to form mesoporous structures during long-term sintering, which affects their cycle stability and capacity performance.
The precursor of sodium ferrophosphate phosphate is prepared by spray drying, solid phase or sol-gel method, and pre-calcination and thermal shock treatment are carried out under the atmosphere of protective gas to regulate the water vapor release rate and phase formation rate, and quickly synthesize the mesoporous Structural sodium ferro pyrophosphate material.
The high specific surface area and high capacity of sodium ferric pyrophosphate phosphate material are achieved, which improves its electrochemical performance and cycle stability, shortens preparation time and saves energy consumption.
Smart Images

Figure CN119143098A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sodium iron phosphate pyrophosphate materials, and in particular to a sodium iron phosphate pyrophosphate material with a mesoporous structure, a preparation method and an application thereof. Background Art
[0002] The cathode material is a key component that determines the electrochemical performance, safety and other important properties of sodium-ion batteries. The sodium iron phosphate pyrophosphate cathode material with an open and stable three-dimensional structure has the advantages of long cycle life, high operating voltage and high safety and stability, and stands out from many iron-based polyanion sodium-ion battery cathode materials.
[0003] Mesoporous structure is very conducive to the deintercalation of ions and improves the capacity. However, in current research and production, in order to improve the cycle stability of the material, a sintering process with slow heating and long-term high-temperature insulation is generally used to prepare larger particles of sodium iron pyrophosphate material. Conventional preparation slowly releases gas during long-term sintering, and mesopores are not easy to produce. Moreover, due to sufficiently long insulation time, the pore structure can easily disappear due to processes such as ion migration. Although the long-term cycle stability is improved, the breakthrough in capacity performance is affected. Summary of the invention
[0004] The purpose of the present invention is to provide a mesoporous sodium iron phosphate pyrophosphate material and a preparation method thereof. The preparation method can quickly synthesize a sodium iron phosphate pyrophosphate material with a mesoporous structure on the surface. The synthesized mesoporous sodium iron phosphate pyrophosphate has a high specific surface area and a high capacity, and can be used as a positive electrode material in sodium ion batteries.
[0005] One of the technical solutions of the present invention is to provide a method for preparing a mesoporous sodium iron phosphate pyrophosphate material, the preparation method comprising the following steps:
[0006] Step 1, preparing a sodium iron pyrophosphate precursor using an iron source, a phosphorus source, a sodium source and a carbon source, wherein the mass of the carbon source is 10%-35% of the total mass, and preparing the sodium iron pyrophosphate precursor using a spray drying method, a solid phase method, a sol-gel method, etc.;
[0007] Step 2, grinding the precursor obtained in step 1, and then pre-calcining it under a protective gas atmosphere;
[0008] Step 3: Under a protective gas atmosphere, place the pre-sintered precursor obtained in step 2 on a heated substrate, apply power to the precursor powder for thermal shock, and obtain a sodium iron pyrophosphate material with a mesoporous structure.
[0009] The present invention performs high-temperature thermal shock on the preheated sodium iron phosphate pyrophosphate precursor, that is, direct current generates Joule heat through a load, which provides energy for the sodium iron phosphate pyrophosphate to form a phase in a short time, and quickly prepares the sodium iron phosphate pyrophosphate material.
[0010] The present invention effectively regulates the water vapor release rate and the phase formation rate through a pre-calcination treatment at a relatively low temperature and a thermal shock treatment at a relatively high temperature, constructs a surface structure with mesopores, and obtains mesoporous sodium iron pyrophosphate.
[0011] Furthermore, in step 1, the iron source is one or more combinations of ferric hydroxide, ferric nitrate, ferric oxalate, ferric chloride, ferric oxide, ferrous oxide, and ferrous oxide.
[0012] Furthermore, in step 1, the phosphorus source is one or more combinations of sodium phosphate, sodium hydrogen phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium pyrophosphate, and disodium dihydrogen pyrophosphate.
[0013] Furthermore, in step 1, the sodium source is one or more combinations of sodium hydroxide, sodium nitrate, sodium oxalate, sodium chloride, sodium phosphate, sodium hydrogen phosphate, sodium dihydrogen phosphate, and disodium hydrogen phosphate.
[0014] Furthermore, the carbon source in step 1 is one or more combinations of reducing carbon sources.
[0015] Furthermore, the reducing carbon source includes one or more combinations of ascorbic acid, glucose, sucrose, citric acid, oxalic acid, ethylene glycol, graphene, and carbon nanotubes.
[0016] Furthermore, before grinding the sodium iron pyrophosphate precursor in step 2, the sodium iron pyrophosphate precursor is dried by vacuum drying at a temperature of 80-120° C. for a drying time of 8-16 hours.
[0017] Furthermore, the pre-sintering treatment temperature in step 2 is 250-400° C. and the duration is 3-7 hours.
[0018] Furthermore, the thermal shock temperature in step 3 is 400-700° C. and the duration is 100-200 s.
[0019] The second technical solution of the present invention is to provide a mesoporous structured sodium iron phosphate pyrophosphate material, which has a mesoporous structure on the surface and a mesopore size of 10-50nm. The mesopores can effectively increase the ion migration rate, thereby improving the electrochemical performance of the sodium iron phosphate pyrophosphate material.
[0020] The third technical solution of the present invention is to provide a mesoporous sodium iron phosphate pyrophosphate material as a positive electrode material. The mesoporous sodium iron phosphate pyrophosphate material obtained in the embodiment has a cycle performance under 1.0C conditions, and the capacity can reach 96 to 100 mAh g -1 .
[0021] Compared with the prior art, the present invention can achieve the following beneficial effects:
[0022] (1) The surface of the sodium iron phosphate pyrophosphate material prepared by the present invention has a mesoporous structure, which makes its specific surface area larger, helps the electrolyte to better penetrate into the interior of the electrode material, ensures a more uniform electrochemical reaction, and helps to improve the efficiency of the electrochemical reaction and the overall energy density of the battery. When it is used as a positive electrode material for a battery, its initial capacity is increased by 4-8 mAh g compared with the existing sodium iron phosphate pyrophosphate. -1 .
[0023] (2) The method of the present invention can greatly shorten the time for preparing sodium iron pyrophosphate material, thereby saving energy consumption in the preparation process. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 is a scanning electron microscope image of Example 1 of the present invention, with a magnification of 20,000 times;
[0025] Figure 2 This is a cycle performance diagram of Example 1 of the present invention under 1.0C conditions;
[0026] Figure 3 is a scanning electron microscope image of Example 2 of the present invention, with a magnification of 20,000 times;
[0027] Figure 4 This is a cycle performance diagram of Example 2 of the present invention under 1.0C conditions;
[0028] Figure 5 is a scanning electron microscope image of Example 3 of the present invention, with a magnification of 20,000 times;
[0029] Figure 6 This is a cycle performance diagram of Example 3 of the present invention under 1.0C conditions;
[0030] Figure 7 is a scanning electron microscope image of Example 4 of the present invention, with a magnification of 20,000 times;
[0031] Figure 8 is a cycle performance diagram of Example 4 of the present invention under 1.0C conditions;
[0032] Fig. 9is a scanning electron microscope image of Example 5 of the present invention, with a magnification of 20,000 times;
[0033] Fig.10 is a cycle performance diagram of Example 5 of the present invention under 1.0C conditions;
[0034] Fig.11 is a scanning electron microscope image of Example 6 of the present invention, with a magnification of 20,000 times;
[0035] Fig.12 This is a cycle performance diagram of Example 6 of the present invention under 1.0C conditions;
[0036] Fig.13 is a scanning electron microscope image of Example 7 of the present invention, with a magnification of 20,000 times;
[0037] Fig.14 This is a cycle performance diagram of Example 7 of the present invention under 1.0C conditions;
[0038] Fig.15 is a scanning electron microscope image of Example 8 of the present invention, with a magnification of 20,000 times;
[0039] Fig.16 This is a cycle performance diagram of Example 8 of the present invention under 1.0C conditions;
[0040] Fig.17 is a scanning electron microscope image of Example 9 of the present invention, with a magnification of 20,000 times;
[0041] Fig.18 is a cycle performance diagram of Example 9 of the present invention under 1.0C conditions;
[0042] Fig.19 is a scanning electron microscope image of Comparative Example 1, with a magnification of 20,000 times;
[0043] Fig. 20 This is the cycle performance diagram of Comparative Example 1 under 1.0C conditions;
[0044] Fig.21 is a scanning electron microscope image of Comparative Example 2, with a magnification of 20,000 times;
[0045] Fig. 22 This is the cycle performance diagram of Comparative Example 2 under 1.0C conditions;
[0046] Fig.23 is a scanning electron microscope image of Comparative Example 3, with a magnification of 20,000 times;
[0047] Fig.24 This is the cycle performance diagram of Comparative Example 3 under 1.0C conditions. DETAILED DESCRIPTION
[0048] The following examples are used to further illustrate the present invention. Their purpose is to illustrate the present invention but should not be construed as limiting the scope of the present invention.
[0049] In the present invention, the heating substrate is common knowledge in the art, and is generally carbon cloth, carbon sheet, carbon felt or gold foil.
[0050] In the present invention, the protective gas is common knowledge in the art, and is generally nitrogen, argon or a mixture of nitrogen and argon.
[0051] The raw materials used in the present invention, unless otherwise specified, are conventional commercially available products; the methods used in the present invention, unless otherwise specified, are conventional methods in the art.
[0052] The embodiments of the present invention are further described below with reference to a plurality of embodiments.
[0053] It should be clear that the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.
[0054] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0055] Example 1
[0056] The mesoporous sodium iron phosphate pyrophosphate material of this embodiment is prepared according to the following steps:
[0057] Step 1: Prepare sodium ferric pyrophosphate precursor by spray drying. Add ferric hydroxide, sodium phosphate and sodium hydroxide in molar ratio into deionized water, add 20% ascorbic acid as carbon source, and disperse evenly by ultrasonic treatment. -1 The precursor powder was prepared by spray drying at a flow rate of .
[0058] Step 2: Grind the precursor prepared by the spray drying method, and then place it in a tube furnace under the protection of an argon atmosphere and pre-calcine it at 250° C. for 7 hours to obtain a dark yellow powder.
[0059] Step 3, the thermal shock process is carried out in an argon environment, and a 5*2.5 cm carbon cloth is selected as the heating substrate. The preheated precursor powder is ground, and 50 mg is placed on the heating substrate. The thermal shock temperature is 400°C, and the preheated precursor powder is subjected to a rapid thermal shock for 200 seconds to obtain the finished product sodium iron pyrophosphate. Figure 1 This is the SEM image of the sodium iron pyrophosphate material with a mesoporous structure that was quickly synthesized by thermal shock using a precursor prepared by spray drying as a raw material in this example. It can be found that the surface of the particles is distributed with a mesoporous structure with a diameter of 20-35 nm.
[0060] Step 4, assemble the prepared materials into button cells and test the electrochemical performance. Weigh Super P, PVDF, and the finished product sodium ferric phosphate pyrophosphate in proportion, mix with an appropriate amount of 1-methyl-2-pyrrolidone (NMP), stir on a magnetic stirrer for 3 hours to obtain a positive electrode slurry, evenly coat it on aluminum foil, and obtain a positive electrode sheet after vacuum drying and cutting. After assembling into a button cell in an argon environment, test its electrochemical performance. Figure 2 The cyclic performance diagram of the sodium iron phosphate pyrophosphate material obtained in this example under 1.0C conditions is shown, and the capacity can reach 97 mAh g -1 .
[0061] Example 2
[0062] The mesoporous sodium iron phosphate pyrophosphate material of this embodiment is prepared according to the following steps: Step 1, using a spray drying method to prepare a sodium iron phosphate pyrophosphate precursor, ferric oxalate, sodium dihydrogen phosphate, and sodium oxalate are dissolved in deionized water according to a molar ratio, and 25% of the total mass of oxalic acid is added as a carbon source and ultrasonic treatment is performed to disperse it uniformly. The above solution is heated at 110°C for 150 ml h -1 The precursor powder was prepared by spray drying at a flow rate of .
[0063] Step 2: Grind the precursor prepared by the spray drying method, and then place it in a tube furnace under the protection of an argon atmosphere and pre-calcine it at 300° C. for 5 h to obtain a dark yellow powder.
[0064] Step 3: The thermal shock process is carried out in an argon environment, and a 5*2.5 cm carbon cloth is selected as the heating substrate. The preheated precursor powder is ground, and 50 mg is placed on the heating substrate. The thermal shock temperature is 550°C, and the preheated precursor powder is subjected to a rapid thermal shock for 150 seconds to obtain the finished product of sodium iron pyrophosphate. Figure 3 This is the SEM image of the sodium iron pyrophosphate material with a mesoporous structure that was quickly synthesized by thermal shock using a precursor prepared by spray drying as a raw material in this example. It can be found that the surface of the particles is distributed with a mesoporous structure with a diameter of 15-30 nm.
[0065] Step 4, assemble the prepared materials into button cells and test the electrochemical performance. Weigh Super P, PVDF, and the finished product sodium ferric phosphate pyrophosphate in proportion, mix with an appropriate amount of 1-methyl-2-pyrrolidone (NMP), stir on a magnetic stirrer for 3 hours to obtain a positive electrode slurry, evenly coat it on aluminum foil, and obtain a positive electrode sheet after vacuum drying and cutting. After assembling into a button cell in an argon environment, test its electrochemical performance. Figure 4 The cycle performance diagram of the sodium iron phosphate pyrophosphate material obtained in this example under 1.0C conditions is as high as 96 mAh g -1 .
[0066] Example 3
[0067] The mesoporous sodium iron phosphate pyrophosphate material of this embodiment is prepared according to the following steps: Step 1, using a spray drying method to prepare a sodium iron phosphate pyrophosphate precursor, ferrous oxide, disodium dihydrogen pyrophosphate, and sodium hydrogen phosphate are dissolved in deionized water in a molar ratio, and 35% of the total mass of citric acid and graphene are added as carbon sources, and ultrasonic treatment is performed to disperse them uniformly. The above solution is heated at 110°C for 150 ml h -1 The precursor powder was prepared by spray drying at a flow rate of .
[0068] Step 2: Grind the precursor prepared by the spray drying method, and then place it in a tube furnace under the protection of an argon atmosphere and pre-calcine it at 400° C. for 3 h to obtain a dark yellow powder.
[0069] Step 3: The thermal shock process is carried out in an argon environment, and a 5*2.5 cm carbon cloth is selected as the heating substrate. The preheated precursor powder is ground, and 50 mg is placed on the heating substrate. The thermal shock temperature is 700°C, and the preheated precursor powder is subjected to a rapid thermal shock for 100 seconds to obtain the finished product of sodium iron pyrophosphate. Figure 5 This is the SEM image of the sodium iron pyrophosphate material with a mesoporous structure that was quickly synthesized by thermal shock using a precursor prepared by spray drying as a raw material in this example. It can be found that mesoporous structures with a diameter of 10-25 nm are distributed on the surface of the particles.
[0070] Step 4, assemble the prepared materials into button cells and test the electrochemical performance. Weigh Super P, PVDF, and the finished product sodium ferric phosphate pyrophosphate in proportion, mix with an appropriate amount of 1-methyl-2-pyrrolidone (NMP), stir on a magnetic stirrer for 3 hours to obtain a positive electrode slurry, evenly coat it on aluminum foil, and obtain a positive electrode sheet after vacuum drying and cutting. After assembling into a button cell in an argon environment, test its electrochemical performance. Figure 6The cycle performance diagram of the sodium iron phosphate pyrophosphate material obtained in this example under 1.0C conditions, the capacity can reach 100 mAh g -1 .
[0071] Example 4
[0072] The mesoporous structured sodium iron phosphate pyrophosphate material of this embodiment is prepared according to the following steps: Step 1, using a solid phase method to prepare a sodium iron phosphate pyrophosphate precursor, adding ferric nitrate, sodium hydrogen phosphate, disodium hydrogen phosphate, and ethylene glycol in a molar ratio into a ball mill, and adding 30% of the total mass of glucose as a carbon source, and adding an appropriate amount of deionized water grinding balls, and ball milling at a speed of 300r / min in a ball mill for 6h, and then placing it in a vacuum oven at 80°C for 16h to obtain a precursor powder.
[0073] Step 2: Grind the precursor prepared by the solid phase method, and then place it in a tube furnace under the protection of argon atmosphere, and pre-calcine it at 270° C. for 6.5 hours to obtain a dark yellow powder.
[0074] Step 3, the thermal shock process is carried out in an argon environment, and a 5*2.5 cm carbon cloth is selected as the heating substrate. The preheated precursor powder is ground, and 50 mg is placed on the heating substrate. The thermal shock temperature is 450°C, and the preheated precursor powder is subjected to rapid thermal shock for 180 seconds to obtain the finished product sodium iron pyrophosphate. Figure 7 This is the SEM image of the sodium iron pyrophosphate material with a mesoporous structure that was rapidly synthesized by thermal shock using a precursor prepared by a solid phase method as a raw material. It can be found that the surface of the particles is distributed with a mesoporous structure with a diameter of 20-40 nm.
[0075] Step 4, assemble the prepared materials into button cells and test the electrochemical performance. Weigh Super P, PVDF, and the finished product sodium ferric phosphate pyrophosphate in proportion, mix with an appropriate amount of 1-methyl-2-pyrrolidone (NMP), stir on a magnetic stirrer for 3 hours to obtain a positive electrode slurry, evenly coat it on aluminum foil, and obtain a positive electrode sheet after vacuum drying and cutting. After assembling into a button cell in an argon environment, test its electrochemical performance. Figure 8 The cyclic performance diagram of the sodium iron phosphate pyrophosphate material obtained in this example under 1.0C conditions is shown, and the capacity can reach 98 mAh g -1 .
[0076] Example 5
[0077] The mesoporous sodium iron phosphate pyrophosphate material of this embodiment is prepared according to the following steps:
[0078] Step 1, using the solid phase method to prepare the sodium iron pyrophosphate precursor, add ferrosilicate, sodium dihydrogen phosphate, and disodium hydrogen phosphate in a molar ratio into a ball mill, add 10% of the total mass of sucrose and carbon nanotubes as carbon sources, and add an appropriate amount of deionized water grinding balls, ball mill at a speed of 300r / min in a ball mill for 6h, and then place it in a vacuum oven at 100°C for 12h to obtain a precursor powder.
[0079] Step 2: Grind the precursor prepared by the solid phase method, and then place it in a tube furnace under the protection of an argon atmosphere and pre-calcine it at 300° C. for 5 h to obtain a dark yellow powder.
[0080] Step 3: The thermal shock process is carried out in an argon environment, and a 5*2.5 cm carbon cloth is selected as the heating substrate. The preheated precursor powder is ground, and 50 mg is placed on the heating substrate. The thermal shock temperature is 550°C, and the preheated precursor powder is subjected to a rapid thermal shock for 150 seconds to obtain the finished product of sodium iron pyrophosphate. Fig. 9 This is the SEM image of the sodium iron pyrophosphate material with a mesoporous structure that was rapidly synthesized by thermal shock using a precursor prepared by a solid phase method as a raw material. It can be found that a mesoporous structure with a diameter of 30-45 nm is distributed on the surface of the particles.
[0081] Step 4, assemble the prepared materials into button cells and test the electrochemical performance. Weigh Super P, PVDF, and the finished product sodium ferric phosphate pyrophosphate in proportion, mix with an appropriate amount of 1-methyl-2-pyrrolidone (NMP), stir on a magnetic stirrer for 3 hours to obtain a positive electrode slurry, evenly coat it on aluminum foil, and obtain a positive electrode sheet after vacuum drying and cutting. After assembling into a button cell in an argon environment, test its electrochemical performance. Fig.10 The cycle performance diagram of the sodium iron phosphate pyrophosphate material obtained in this example under 1.0C conditions is as high as 99 mAh g -1 .
[0082] Example 6
[0083] The mesoporous sodium iron phosphate pyrophosphate material of this embodiment is prepared according to the following steps:
[0084] Step 1, using a solid phase method to prepare a sodium iron pyrophosphate precursor, add ferric nitrate, sodium pyrophosphate, and sodium nitrate into a ball mill in a molar ratio, add 10% of the total mass of citric acid as a carbon source, and add an appropriate amount of deionized water grinding balls, ball mill in a ball mill at a speed of 300 r / min for 6 hours, and then place it in a vacuum oven at 120°C for 8 hours to obtain a precursor powder.
[0085] Step 2: Grind the precursor prepared by the solid phase method, and then place it in a tube furnace under the protection of argon atmosphere, and pre-calcine it at 330° C. for 3.5 hours to obtain a dark yellow powder.
[0086] Step 3: The thermal shock process is carried out in an argon environment, and a 5*2.5 cm carbon cloth is selected as the heating substrate. The preheated precursor powder is ground, and 50 mg is placed on the heating substrate. The thermal shock temperature is 650°C, and the preheated precursor powder is subjected to a rapid thermal shock for 120 seconds to obtain the finished product of sodium iron pyrophosphate. Fig.11 This is the SEM image of the sodium iron phosphate pyrophosphate material with a mesoporous structure that was rapidly synthesized by thermal shock using a precursor prepared by a solid phase method as a raw material. It can be found that a mesoporous structure with a diameter of 30-40 nm is distributed on the surface of the particles.
[0087] Step 4, assemble the prepared materials into button cells and test the electrochemical performance. Weigh Super P, PVDF, and the finished product sodium ferric phosphate pyrophosphate in proportion, mix with an appropriate amount of 1-methyl-2-pyrrolidone (NMP), stir on a magnetic stirrer for 3 hours to obtain a positive electrode slurry, evenly coat it on aluminum foil, and obtain a positive electrode sheet after vacuum drying and cutting. After assembling into a button cell in an argon environment, test its electrochemical performance. Fig.12 The cycle performance diagram of the sodium iron phosphate pyrophosphate material obtained in this example under 1.0C conditions is as high as 96 mAh g -1 .
[0088] Example 7
[0089] The mesoporous sodium iron phosphate pyrophosphate material of this embodiment is prepared according to the following steps:
[0090] Step 1: Prepare sodium iron phosphate pyrophosphate precursor using the sol-gel method. Add ferric chloride, sodium dihydrogen phosphate, and sodium chloride in molar ratio to deionized water, and add 10% of the total mass of graphene and ascorbic acid as carbon sources; stir for 1 hour to keep the solution transparent. Subsequently, add an appropriate amount of ethylene glycol to the solution and heat it to 120°C for 1 hour to obtain a gel. Place the gel in a vacuum oven at 80°C and dry it for 16 hours to obtain a precursor powder.
[0091] Step 2: Grind the precursor prepared by the sol-gel method, and then place it in a tubular furnace under the protection of an argon atmosphere and pre-calcine it at 260° C. for 6.5 h to obtain a dark yellow powder.
[0092] Step 3, the thermal shock process is carried out in an argon environment, and a 5*2.5 cm carbon cloth is selected as the heating substrate. The preheated precursor powder is ground, and 50 mg is placed on the heating substrate. The thermal shock temperature is 400°C, and the preheated precursor powder is subjected to a rapid thermal shock for 200 seconds to obtain the finished product sodium iron pyrophosphate. Fig.13 This is the SEM image of the sodium iron pyrophosphate material with a mesoporous structure that was quickly synthesized by thermal shock using a precursor prepared by the sol-gel method in this example. It can be found that the surface of the particles is distributed with a mesoporous structure with a diameter of 35-50 nm.
[0093] Step 4, assemble the prepared materials into button cells and test the electrochemical performance. Weigh Super P, PVDF, and the finished product sodium ferric phosphate pyrophosphate in proportion, mix with an appropriate amount of 1-methyl-2-pyrrolidone (NMP), stir on a magnetic stirrer for 3 hours to obtain a positive electrode slurry, evenly coat it on aluminum foil, and obtain a positive electrode sheet after vacuum drying and cutting. After assembling into a button cell in an argon environment, test its electrochemical performance. Fig.14 The cyclic performance diagram of the sodium iron phosphate pyrophosphate material obtained in this example under 1.0C conditions is shown, and the capacity can reach 97 mAh g -1 .
[0094] Example 8
[0095] The mesoporous sodium iron phosphate pyrophosphate material of this embodiment is prepared according to the following steps:
[0096] Step 1: Prepare sodium iron phosphate pyrophosphate precursor using the sol-gel method. Add ferric oxide, sodium hydrogen phosphate, and disodium hydrogen phosphate in molar ratio to deionized water, and add 35% of the total mass of glucose as a carbon source and stir for 1 hour to keep the solution transparent. Subsequently, add an appropriate amount of ethylene glycol to the solution and heat it to 120°C for 1 hour to obtain a gel. Place the gel in a vacuum oven at 100°C and dry it for 12 hours to obtain a precursor powder.
[0097] Step 2: Grind the precursor prepared by the sol-gel method, and then place it in a tubular furnace under the protection of an argon atmosphere and pre-calcine it at 300° C. for 5 h to obtain a dark yellow powder.
[0098] Step 3: The thermal shock process is carried out in an argon environment, and a 5*2.5 cm carbon cloth is selected as the heating substrate. The preheated precursor powder is ground, and 50 mg is placed on the heating substrate. The thermal shock temperature is 550°C, and the preheated precursor powder is subjected to a rapid thermal shock for 150 seconds to obtain the finished product of sodium iron pyrophosphate. Fig.15This is the SEM image of the sodium iron pyrophosphate material with a mesoporous structure that was quickly synthesized by thermal shock using a precursor prepared by the sol-gel method in this example. It can be found that mesoporous structures with a diameter of 10-25 nm are distributed on the surface of the particles.
[0099] Step 4, assemble the prepared materials into button cells and test the electrochemical performance. Weigh Super P, PVDF, and the finished product sodium ferric phosphate pyrophosphate in proportion, mix with an appropriate amount of 1-methyl-2-pyrrolidone (NMP), stir on a magnetic stirrer for 3 hours to obtain a positive electrode slurry, evenly coat it on aluminum foil, and obtain a positive electrode sheet after vacuum drying and cutting. After assembling into a button cell in an argon environment, test its electrochemical performance. Fig.16 The cyclic performance diagram of the sodium iron phosphate pyrophosphate material obtained in this example under 1.0C conditions is shown, and the capacity can reach 98 mAh g -1 .
[0100] Example 9
[0101] The mesoporous sodium iron phosphate pyrophosphate material of this embodiment is prepared according to the following steps:
[0102] Step 1: Prepare sodium iron phosphate pyrophosphate precursor using the sol-gel method. Add ferric hydroxide, sodium dihydrogen phosphate, and sodium hydroxide to deionized water in molar ratio, and add 10% carbon nanotubes as a carbon source and stir for 1 hour to keep the solution transparent. Then, add an appropriate amount of ethylene glycol to the solution and heat it to 120°C for 1 hour to obtain a gel. Place the gel in a vacuum oven at 120°C and dry it for 8 hours to obtain a precursor powder.
[0103] Step 2: Grind the precursor prepared by the sol-gel method, and then place it in a tubular furnace under the protection of an argon atmosphere and pre-calcine it at 340° C. for 3.5 h to obtain a dark yellow powder.
[0104] Step 3: The thermal shock process is carried out in an argon environment, and a 5*2.5 cm carbon cloth is selected as the heating substrate. The preheated precursor powder is ground, and 50 mg is placed on the heating substrate. The thermal shock temperature is 700°C, and the preheated precursor powder is subjected to a rapid thermal shock for 100 seconds to obtain the finished product of sodium iron pyrophosphate. Fig.17 This is the SEM image of the sodium iron pyrophosphate material with a mesoporous structure that was quickly synthesized by thermal shock using a precursor prepared by the sol-gel method in this example. It can be found that the surface of the particles is distributed with a mesoporous structure with a diameter of 35-50 nm.
[0105] Step 4, assemble the prepared materials into button cells and test the electrochemical performance. Weigh Super P, PVDF, and the finished product sodium ferric phosphate pyrophosphate in proportion, mix with an appropriate amount of 1-methyl-2-pyrrolidone (NMP), stir on a magnetic stirrer for 3 hours to obtain a positive electrode slurry, evenly coat it on aluminum foil, and obtain a positive electrode sheet after vacuum drying and cutting. After assembling into a button cell in an argon environment, test its electrochemical performance. Fig.18 The cyclic performance diagram of the sodium iron phosphate pyrophosphate material obtained in this example under 1.0C conditions is shown, and the capacity can reach 97 mAh g -1 .
[0106] Comparative Example 1
[0107] The sodium iron phosphate pyrophosphate material of this comparative example is prepared according to the following steps:
[0108] Step 1, using a spray drying method to prepare a sodium iron pyrophosphate precursor, the difference from Example 1 is the calcination process in step 3, and the other steps remain unchanged. Step 3, grinding the pre-calcined sample, placing it in a tube furnace under argon atmosphere protection, and pre-calcining it at 400° C. for 10 hours to obtain sodium iron pyrophosphate.
[0109] Fig.19 This is the SEM image of the sodium iron pyrophosphate material synthesized by calcining in an argon atmosphere using a precursor prepared by a spray drying method as a raw material in this embodiment. It can be found that the surface of the particles is smooth. Fig. 20 The cycle performance diagram of the sodium iron phosphate pyrophosphate material obtained in this example under 1.0C conditions, with a capacity of 92 mAh g -1 .
[0110] Comparative Example 2
[0111] The sodium iron phosphate pyrophosphate material of this comparative example is prepared according to the following steps:
[0112] The precursor was prepared by a solid phase method, and the sodium iron phosphate pyrophosphate material was synthesized by a traditional calcination method. The difference from Example 4 was the calcination process in step 3, and the other steps remained unchanged. Step 3, the pre-calcined sample was ground and placed in a tube furnace under argon atmosphere protection, and pre-calcined at 450° C. for 10 hours to obtain sodium iron phosphate pyrophosphate.
[0113] Fig.21 This is the SEM image of the sodium iron pyrophosphate material synthesized by calcining in an argon atmosphere using a precursor prepared by a solid phase method as a raw material in a traditional tube furnace. It can be found that the surface of the particles is smooth. Fig. 22 The cycle performance diagram of the sodium iron phosphate pyrophosphate material obtained in this example under 1.0C conditions, with a capacity of 92 mAh g-1 .
[0114] Comparative Example 3
[0115] The sodium iron phosphate pyrophosphate material of this comparative example is prepared according to the following steps:
[0116] The precursor was prepared by the sol-gel method, and the sodium iron phosphate pyrophosphate material was synthesized by the traditional calcination method. The difference from Example 7 was the calcination process in step 3, and the other steps remained unchanged. Step 3, the pre-calcined sample was ground and placed in a tube furnace under argon atmosphere, pre-calcined at 400° C. for 10 hours to obtain sodium iron phosphate pyrophosphate.
[0117] Fig.23 The SEM image of the sodium iron pyrophosphate material synthesized by calcining the precursor prepared by the sol-gel method in this embodiment as a raw material in a traditional tubular furnace under an argon atmosphere shows that the surface of the particles is smooth. Fig.24 The cycle performance diagram of the sodium iron phosphate pyrophosphate material obtained in this example under 1.0C conditions, with a capacity of 90 mAh g -1 .
[0118] Table 1: Initial specific capacity of batteries prepared from sodium iron phosphate pyrophosphate obtained in Examples 1-9 and Comparative Examples 1-3
[0119]
[0120] Table 1 shows the initial capacity comparison of the thermal shock sample (Example) and the tube furnace sample (Comparative Example) at 1.0C. The initial capacity of the Example is 4-8 mAh g higher than that of the Comparative Example. -1 Compared with the traditional tubular furnace calcination, the rapid synthesis of sodium iron phosphate pyrophosphate materials with mesoporous structure by thermal shock has higher capacity and better electrochemical performance. It is proved that the mesoporous structure designed by thermal shock can improve the efficiency of ion migration, thereby improving the capacity and improving its electrochemical performance, and obtaining sodium iron phosphate pyrophosphate materials with excellent electrochemical performance.
[0121] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a mesoporous sodium iron pyrophosphate material, characterized in that: The following steps are involved: Step 1, preparing a sodium iron pyrophosphate precursor using an iron source, a phosphorus source, a sodium source and a carbon source, wherein the mass of the carbon source accounts for 10% to 35% of the total mass; Step 2, grinding the sodium iron pyrophosphate precursor, and then pre-calcining it under a protective gas atmosphere; Step 3: Under a protective gas atmosphere, place the pre-sintered precursor obtained in step 2 on a heated substrate, apply power to thermally shock the precursor powder, and obtain a sodium iron pyrophosphate material with a mesoporous structure.
2. The method for preparing the mesoporous sodium iron pyrophosphate material according to claim 1, characterized in that: The preparation method of the sodium iron phosphate pyrophosphate precursor in step 1 is spray drying method, solid phase method and sol-gel method.
3. The method for preparing the mesoporous sodium iron pyrophosphate material according to claim 1, characterized in that: In step 1, the iron source is one or more combinations of ferric hydroxide, ferric nitrate, ferric oxalate, ferric chloride, ferric oxide, ferrous oxide, and ferrous oxide; In step 1, the phosphorus source is one or more combinations of sodium phosphate, sodium hydrogen phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium pyrophosphate, and disodium dihydrogen pyrophosphate; In step 1, the sodium source is one or more combinations of sodium hydroxide, sodium nitrate, sodium oxalate, sodium chloride, sodium phosphate, sodium hydrogen phosphate, sodium dihydrogen phosphate, and disodium hydrogen phosphate.
4. The method for preparing the mesoporous sodium iron pyrophosphate material according to claim 1, characterized in that: The carbon source in step 1 is a reducing carbon source.
5. The method for preparing the mesoporous sodium iron pyrophosphate material according to claim 4, characterized in that: The reducing carbon source is one or more combinations of ascorbic acid, glucose, sucrose, citric acid, oxalic acid, ethylene glycol, graphene, and carbon nanotubes.
6. The method for preparing the mesoporous sodium iron pyrophosphate material according to claim 1, characterized in that: Before grinding the sodium iron pyrophosphate precursor in step 2, the sodium iron pyrophosphate precursor is dried by vacuum drying at a temperature of 80-120° C. for a drying time of 8-16 hours.
7. The method for preparing the mesoporous sodium iron pyrophosphate material according to claim 1, characterized in that: The pre-sintering treatment temperature in step 2 is 250-400° C. and the duration is 3-7 hours.
8. The method for preparing the mesoporous sodium iron pyrophosphate material according to claim 1, characterized in that: The thermal shock temperature in step 3 is 400-700° C. and the duration is 100-200 seconds.
9. A mesoporous sodium iron pyrophosphate material prepared by the method of claim 1.
10. Use of the mesoporous sodium iron phosphate pyrophosphate material according to claim 9 as a positive electrode material.
Citation Information
Patent Citations
Preparation method for synthesizing lithium iron phosphate positive electrode material through rapid high-temperature thermal shock method and application thereof
CN113540410A
Positive pole piece and preparation method thereof, energy storage device and power utilization device
CN116741988A
Preparation method of spherical ferric sodium pyrophosphate positive electrode material
CN117819507A
Sodium ferric pyrophosphate sodium ion battery positive electrode material and preparation method thereof
CN118047362A
Method for synthesizing carbon-coated ferric sodium pyrophosphate based on microwave method
CN118405679A
Cited By
Sodium ferric phosphate pyrophosphate composite positive electrode material and preparation method thereof
CN119812262A
Quickly synthesized ferric sodium pyrophosphate electrode material, preparation method thereof and positive electrode
CN121202094A
